2015
DOI: 10.17219/acem/40453
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oleuropein on Serum Inflammatory Cytokines and Histopathological Changes in Rats with Pancreatitis

Abstract: The experimental model used in this study showed to be appropriate for creation of acute pancreatitis. It was concluded that oleuropein as a prophylactic treatment has no protective effect on serum proinflammatory and anti-inflammatory cytokines as well as pancreatic tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Data recorded in vivo for an OLE-mediated effect on circulating IL-6 led to inconclusive results. In an in vivo model of acute pancreatitis, OLE showed no prophylactic effect in terms of reduction in serum IL-6 [89], but in LPS-induced sepsis [80], in cyclophosphamide and epirubicin combined treatment toxicity [90], in myocardial ischemia/reperfusion [81], and in experimental autoimmune myocarditis [91], an OLE anti-inflammatory effect manifested in part as a decrease in IL-6 serum level. An analogous reduction in plasma IL-6 levels was mediated by OLE in a model of sepsis-induced myocardial injury [92].…”
Section: Il-6mentioning
confidence: 99%
See 1 more Smart Citation
“…Data recorded in vivo for an OLE-mediated effect on circulating IL-6 led to inconclusive results. In an in vivo model of acute pancreatitis, OLE showed no prophylactic effect in terms of reduction in serum IL-6 [89], but in LPS-induced sepsis [80], in cyclophosphamide and epirubicin combined treatment toxicity [90], in myocardial ischemia/reperfusion [81], and in experimental autoimmune myocarditis [91], an OLE anti-inflammatory effect manifested in part as a decrease in IL-6 serum level. An analogous reduction in plasma IL-6 levels was mediated by OLE in a model of sepsis-induced myocardial injury [92].…”
Section: Il-6mentioning
confidence: 99%
“…An analogous reduction in plasma IL-6 levels was mediated by OLE in a model of sepsis-induced myocardial injury [92]. In the limits of biological differences of used animals and experimental models, discrepant results cannot be explained in terms of the variability of the administered doses, since in acute pancreatitis, experimental autoimmune myocarditis, and sepsis-induced myocardial injury models, researchers employed a 20 mg/kg dose of OLE, with 25 and 50 mg/kg doses used only in LPS-induced sepsis [80,89,91,92].…”
Section: Il-6mentioning
confidence: 99%
“…The underlying mechanisms of inflammation and necrosis are not fully understood, but it has generally been recognized that activated leukocytes play a significant role in the pathogenesis of inflammation. Serum concentrations of pro-inflammatory cytokines, such as tumor necrosis factor α, and interleukins, such as interleukin-1 beta (IL-1), interleukin-6 (IL-6), and interleukin-8 (IL-8), were significantly higher in severe pancreatitis compared with mild pancreatitis [ 27 , 28 ].…”
Section: Acute Pancreatitismentioning
confidence: 99%
“…Oleuropein (23) is a glycosylated seco-iridoid obtained from Olea europaea L., and has been shown to produce antioxidant, anti-atherosclerotic, and anti-inflammatory activities (Impellizzeri et al, 2011b). Several studies have reported that oleuropein can attenuate the levels of pro-inflammatory cytokines in various experimental models such as carrageenan-induced pleurisy, DSS (dextran sulfate sodium)-induced chronic colitis (Giner et al, 2011), doxorubicin-induced cardiomyopathy (Andreadou et al, 2014), myocardial infarction (Janahmadi et al, 2015) and BPDO (bile-pancreatic duct obstruction)-induced pancreatitis (Caglayan et al, 2015). Impellizzeri et al, (Impellizzeri et al, 2011a), showed that oleuropein significantly attenuated the release of TNF-α and IL-1β in the pleural exudates in a carrageenan-induced pleurisy model.…”
Section: Iridoid Glycosidesmentioning
confidence: 99%